The Loss of Diversity in the Anthropocene Biological and Cultural Dimensions - Eriksen, Thomas Hylland (Frontiers in Political Science, 2021)
Theories of nationalism emphasise its standardising effects. Ernest Gellner compared the pre-nationalist world to a painting by Kokoschka (a colour extravaganza) and the world of nationalism as one by Modigliani (calm, monochrome surfaces), while Benedict Anderson showed how the standardisation of language through the medium of printing was a condition for shared national identities. In this article, homogenisation remains a concern, but the empirical framework differs from that of late 20th century theory. Taking its cue from Charles Mann’s 1493, a study of the world after Columbus where the term Homogenocene was proposed, the article shows how homogenisation is a key element in modernity, and analyses some implications of its recent acceleration. The effects of economic globalisation are detrimental to both biological and cultural diversity, since the Anthropocene era does not only refer to a reduction of biological diversity but also the incorporation of cultural groups into market economies, the loss of languages and of traditional livelihoods. The article then briefly surveys some responses to the upscaling of economies, the flattening of ecosystems and the growing power of corporations. The loss of flexibility is countered in a number of ways, from attempts to restore damaged ecosystems to groups defending their cultural and political autonomy. The analysis argues for a broad definition of politics (seen as the political), thereby questioning the ability of the state to solve the dilemma, which is a dual one relating simultaneously to cultural and biological loss. The conclusion is that upscaling (e.g., to the global system) is usually part of the problem rather than the solution, and that sideways scaling may address the shortcomings of downscaling (e.g., to the community level).